2023
DOI: 10.1007/s10067-023-06599-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular manifestations in idiopathic inflammatory myopathies

Abstract: Cardiovascular involvement in idiopathic inflammatory myopathies (IIM) is an understudied area which is gaining increasing recognition in recent times. Recent advances in imaging modalities and biomarkers have allowed the detection of subclinical cardiovascular manifestations in IIM. However, despite the availability of these tools, the diagnostic challenges and underestimated prevalence of cardiovascular involvement in these patients remain significant. Notably, cardiovascular involvement remains one of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 104 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…Cardiovascular complications are prevalent among patients with idiopathic inflammatory myopathies, ranging from 67 to 75 percent. Among the patients in this study, 14.66% had cardiac complications, falling under the broad category of cardiac manifestations (22). Furthermore, the prevalence of auto-antibodies in the Prevision cohort offers contrasts when compared to the literature.…”
Section: Discussionmentioning
confidence: 70%
“…Cardiovascular complications are prevalent among patients with idiopathic inflammatory myopathies, ranging from 67 to 75 percent. Among the patients in this study, 14.66% had cardiac complications, falling under the broad category of cardiac manifestations (22). Furthermore, the prevalence of auto-antibodies in the Prevision cohort offers contrasts when compared to the literature.…”
Section: Discussionmentioning
confidence: 70%
“…However, myocardial involvement (MI) has gradually become another research focus in recent years. Due to different populations and diagnostic criteria, the incidence of MI in IIMs patients ranged from 5.5% to over 50%, which is frequently subclinical in its initial stage [ 11 13 ]. In preceding studies, multiple clinical and laboratory factors have been identified as risk factors for MI [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%